Relação do capital cultural e da competência em informação para o acesso às redes sociais sobre informação científica - Coelho, Vânia Lúcia (2017)
The internet is recognized as one of the main sources of information for its users. It is also known that in this virtual world, millions of people daily access social networks like Facebook. Given this situation, it is proposed to reflect on the potential of social networks, specifically Facebook pages, as reliable sources of scientific information. The aim is to analyze processes, social and informational, which would be intrinsically involved in the relevant access to these spaces, using for this purpose, the concepts such as information literacy, cultural capital and social capital. Also seeks to promote a descriptive and exploratory analysis of the page "Science Today" and, from it and the work of Tomaél, Alcará and Silva (2008), define a set of criteria to evaluate the quality of a Facebook page as a source of scientific information. Finally, through questionnaire analysis sent to fans of the page in question, try to reflect on the influence of the level of education of users access to pages with scientific themes on Facebook. The results aim to support the hypothesis that, in the context of the scientific nature of pages that meet the criteria of reliability, on Facebook, access is mainly for users of higher levels of education, relating the level of education to the concepts of cultural capital and informational literacy. It is concluded that concepts such as information competence and cultural capital, acquired by the subjects, are determinant in the effective use of social networks as reliable sources of dissemination of scientific information.